Magnetic polymer-silica composites as bioluminescent sensors for bilirubin detection; Materials Chemistry and Physics; Vol. 183 - Timin A. S. Aleksandr Sergeevich; Solomonov A. V. Alexey; Kumagai A. Akiko; Miyawaki A. Atsushi; Khashirova S. Yu. Svetlana; Zhansitov A. Azamat; Rumyantsev E. V. Evgeniy (2016, 2016)
Title screen